Ambulatory Phlebectomy and Sclerotherapy as Tools for the Treatment of Varicose Veins and Telangiectasias - Andrews, R. Hampton; Dixon, Robert G. (Seminars in Interventional Radiology, 2021)
Treatment of chronic venous disease is a fascinating and rewarding undertaking. Once the truncal reflux is addressed, several options are available that can be used to treat the associated ulcers, varicosities, reticular veins, and telangiectasias. This review will focus on two widely employed procedures: ambulatory phlebectomy and sclerotherapy.
Keywords: phlebectomy; microphlebectomy; ambulatory phlebectomy; sclerotherapy; varicose veins; telangiectasias; interventional radiology